Tissue-Specific Metabolic Profile Study of Moringa oleifera L. Using Nuclear Magnetic Resonance Spectroscopy (Plant Tissue Culture and Biotechnology, 2014)
Moringa oleifera L. an important multipurpose crop, is rich in various phytochemicals: flavonoids, antioxidants, vitamins, minerals and carotenes. The purpose of this study was to profile the groups of metabolites in leaf and stem tissues of M. oleifera. Various sugars, amino acids, and organic acid derivatives were found in all of the M. oleifera tissues with different profiles and/or peak intensities depending on the tissue. 1D proton nuclear magnetic resonance (NMR) was applied for collecting metabolite spectra. Approximately 30 metabolites with 2 unknown peaks were identified with Chenomx and verified with MMCD databases. Among these metabolites, 22 were identified as common in both leaf and stem tissues. Of the remaining 8 metabolites, 4-aminobutyrate, adenosine, guanosine, tyrosine, and p-cresol were found only in leaf tissues; however, glutamate, glutamine, and tryptophan were found only in stem tissues. Biochemical pathway analysis revealed that 28 identified metabolites were interconnected with 36 different pathways as well as related to different fatty acids and secondary metabolite-synthesis biochemical pathways. It is well known that different tissues of M. oleifera have nutritional, medicinal, and therapeutic values; therefore, our main objective is to provide a publicly available M. oliefera tissue specific metabolite database. Plant Tissue Cult. & Biotech. 24(1): 77-86, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19214